(untitled) (European Journal of Marketing and Economics, 2026)
This study examines how geospatial analytics can support convenience retail expansion decisions in Ecuador. Using a mixed-methods design, we combine secondary demographic and points-of-interest data with GIS-based suitability mapping and qualitative insights from industry stakeholders to identify high-potential retail zones and translate them into actionable site-screening criteria. Results indicate that demand density, accessibility, and competitive configuration jointly shape location attractiveness, while mobility and urban form introduce boundary effects that standard isochrone catchments may overlook. The paper contributes a replicable location-intelligence framework for data-constrained emerging markets and derives managerial implications for network rollout, format placement, and risk reduction in expansion planning. This article is based on the research conducted for the MBA program, defended in 2025, at the Universidad Internacional de Valencia (VIU). The present manuscript is an adapted version of that academic work, and all institutional affiliation and academic context are acknowledged accordingly.